Organizing competition for the market - Elisabetta Iossa; Patrick Rey; Michael Waterson (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2019)
The paper studies competition for the market in a setting where incumbents (and, to a lesser extent, neighboring incumbents) benefit from a cost advantage. The paper first compares the outcome of staggered and synchronous tenders, before drawing the implications for market design. We find that the timing of tenders should depend on the likelihood of monopolization. When monopolization is expected, synchronous tendering is preferable, as it strengthens the pressure that entrants exercise on the monopolist. When instead other firms remain active, staggered tendering is preferable, as it maximizes the competitive pressure that comes from the other firms.
Keywords: D44; D47; H40; H57; L43; L51; R48; 330; Dynamic procurement; incumbency advantage; localmonopoly; competition; asymmetric auctions; synchronous contracts; staggered contracts